IMPACT OF COVID-19 CASES ON ONLINE SEARCHES FOR COGNITIVE SYMPTOMS AND PERSISTENT COVID-19 SYMPTOMS IN BRAZIL - da Silva, Kelly; Santos, Nathália Monteiro; Martins-Filho, Paulo Ricardo; Santos, Franciely Oliveira de Andrade; Souza, Franklim Oliveira; dos Santos, Ronaide Paula; Guedes-Granzotti, Raphaela Barroso; dos Santos, Priscila Lima (ARACÊ, 2024)
Objetive: This study aims to investigate the impact of COVID-19 case numbers on online searches for persistent cognitive symptoms in Brazil. Material and Methods: Utilizing Google Trends™ as a proxy, we analyzed the relative normalized search volume numbers for "memory loss," "forgetfulness," and "persistent COVID-19" from March 2020 to November 2023. Result: Pearson correlation analysis was employed to explore the relationship between search volumes and registered COVID-19 cases per epidemiological week. The study revealed variable search patterns for cognitive symptoms, with "forgetfulness" showing significantly higher search volumes than "memory loss" and "persistent COVID-19." Conclusion: A weak to moderate significant correlation was found between search volumes for cognitive symptoms and the number of COVID-19 cases, particularly in the first two weeks following diagnosis. This indicates an immediate public response to COVID-19 infections with increased online information-seeking behavior regarding cognitive issues. Our findings underscore the significance of infodemiology and infoveillance in monitoring public health concerns, especially during pandemics.